2009
DOI: 10.1897/08-083.1
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological assessment of chemicals using Caenorhabditis elegans and optical oxygen respirometry

Abstract: Oxygen consumption is indicative of an organism's metabolic state, whereby alterations in respiration rate can result from the presence of different stimuli. Here, we develop a novel approach based on quenched fluorescence oxygen sensing and respirometry method for toxicity screening assays using the nematode Caenorhabditis elegans. Previously, C. elegans was established as a useful model in soil and aquatic toxicology studies. For existing toxicology screening approaches with C. elegans, however, the endpoint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…C. elegans is a model organism for research in the fields of developmental biology, molecular biology, neurobiology and toxicology [38-40]. Here, we showed that C. elegans can also be used as a model organism for hypoxia studies.…”
Section: Discussionmentioning
confidence: 88%
“…C. elegans is a model organism for research in the fields of developmental biology, molecular biology, neurobiology and toxicology [38-40]. Here, we showed that C. elegans can also be used as a model organism for hypoxia studies.…”
Section: Discussionmentioning
confidence: 88%
“…Lethality was evaluated as the percent survival of the population based on a previously described method [32]. Fifty L1 larvae stage C. elegans were treated with different concentrations of HAEIBS for 48 hours.…”
Section: Methodsmentioning
confidence: 99%
“…While the majority of applications of optical O 2 micro-respirometry and OCR measurement are cell-based, the method has also been adapted for the monitoring of small aquatic organisms including Daphnia magna, Artemia salina, copepod Tigriopus, zebrafish Danio rerio [3,4]. These model organisms can be used to perform rapid, high-throughput biological testing of potentially hazardous chemicals and environmental samples, as well as basic biological and physiological studies.…”
Section: Respiration Of Small Organisms and Model Animalsmentioning
confidence: 99%
“…This invertebrate organism easily maintained under laboratory conditions is an attractive model for toxicology studies as it is sensitive to a wide range of toxicants, including heavy metals, organic phosphates and pesticides. Such studies have established C. elegans as a powerful model for rapid testing of the toxicity of soil and water samples as well as pharmaceutical compounds [53].…”
Section: Respiration Of Small Organisms and Model Animalsmentioning
confidence: 99%
See 1 more Smart Citation